2017
DOI: 10.1016/j.jaci.2017.01.036
|View full text |Cite
|
Sign up to set email alerts
|

Urban residence, neighborhood poverty, race/ethnicity, and asthma morbidity among children on Medicaid

Abstract: Residence in poor and urban areas is an important risk factor for asthma morbidity, but not for prevalence, among low-income US children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
71
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 145 publications
(80 citation statements)
references
References 23 publications
8
71
1
Order By: Relevance
“…However, despite gaining such high scores and having in mind the high prevalence of severe asthma in passive smokers, strict controlling and educational strategies are still necessitated to control smoking habits and decrease the prevalence of severe asthma in passive smokers. According to some studies, living in urban areas has been known as an important risk factor for paediatric asthma morbidity which is in accordance with our findings. There is an increasing body of evidence suggestive of the role of air pollution in changing the allergenicity of pollens, resulting in increased prevalence of allergic disease in urban areas …”
Section: Discussionsupporting
confidence: 92%
“…However, despite gaining such high scores and having in mind the high prevalence of severe asthma in passive smokers, strict controlling and educational strategies are still necessitated to control smoking habits and decrease the prevalence of severe asthma in passive smokers. According to some studies, living in urban areas has been known as an important risk factor for paediatric asthma morbidity which is in accordance with our findings. There is an increasing body of evidence suggestive of the role of air pollution in changing the allergenicity of pollens, resulting in increased prevalence of allergic disease in urban areas …”
Section: Discussionsupporting
confidence: 92%
“…This may indicate that ED visits are not always associated with uncontrolled asthma as some low income families in the U.S. may use ED for usual asthma care or management that could have been handled at primary care practices. 35,36 It is also worth mentioning the differences in reference timeframes—in the past year for exacerbation indicators vs. previous 4 weeks and 7 days for NAEPP and ACQ respectively, which means that exacerbations have occurred before the measurement of asthma control. Thus, the compelling associations between exacerbation and poorly controlled asthma in this study may suggest inadequate treatment of exacerbation or suboptimal treatment adherence, subsequently leading to poorly controlled asthma.…”
Section: Discussionmentioning
confidence: 99%
“…Some theories for this finding include genetic differences and the contribution of socioeconomic disparities to racial/ethnic disparities. 92 A separate study found African Americans taking ICSs were more likely to have eosinophilic airway inflammation after adjusting for confounders (age, sex, atopic status, body mass index, FEV 1 percent predicted, and uncontrolled asthma). 94 African Americans had lower lung function, higher total serum IgE levels, and worse symptom control compared with white subjects.…”
Section: Health Literacy Health Disparities and Asthmamentioning
confidence: 96%
“…In another study of 1.5 million children with asthma enrolled in Medicaid from 2009-2010, those living in inner-city (poor-urban) areas were found to have a higher risk of asthma-related ED visits and asthma-related hospitalizations, although asthma prevalence was not increased. 92 To improve asthma control for children living in urban areas, Halterman et al 93 examined telemedicine clinician visits and supervised administration of preventative asthma medications in school students with asthma. Urban children with persistent asthma receiving these interventions had fewer asthma ED visits and hospitalizations.…”
Section: Health Literacy Health Disparities and Asthmamentioning
confidence: 99%